EFEKTIVITAS MEDIA PEMBELAJARAN DENTAL SPINNING WHEEL TERHADAP PENINGKATAN PENGETAHUAN PEMELIHARAAN KESEHATAN GIGI DAN MULUT PADA SISWA SEKOLAH DASAR - Hidayat, Aldi; Chaerudin, Denden Ridwan; Ningrum, Nining; Mulyanti, Sri (Poltekkes Kemenkes Bandung, 2025)
Dental and oral hygiene can be done with oral health maintenance efforts to improve the degree of oral health. This is due to a lack of knowledge of oral health maintenance. Efforts to overcome the problem of lack of knowledge about oral health are to implement promotive efforts to improve behavior, namely by educating children of primary school age, delivering good education, especially when conveying information to primary school children, is to use props or media. One of the uses of media used in conducting education is spinning wheels. Spinning wheel is a circular game with various pictures in it, which is rotated around its axis and stops at one of the pictures in the circle. This study aimed to determine the effectiveness of dental spinning wheel on oral health maintenance knowledge in 3rd grade students of Uchuwwatul Islam Elementary School Sukajadi, Bandung City. This research type was pre-experiment research. The sample in this study were 3rd grade students selected using total sampling totaling 30 students. Data collection was obtained directly from respondents in the form of pre test-post test. The results showed that before counseling using dental spinning wheel 50% of students had poor knowledge, after counseling 90% had a good level of knowledge. Statistical test results using the Wilcoxon test showed that the p-value 0.000 (<0.05). The conclusion showed that the dental spinning wheel media is effectively used when counseling is given to increase the knowledge of oral health maintenance of 3rd grade students of SD Uchuwwatul Islam.